Negotiation of Identity in the Main Characters of the Film Green Book (2018): A Communication Accommodation Theory Account - Rennane, Aicha; Mhamedi, Nadhir (Faculty of Letters and Foreign Languages Department of English, 2023)
In 1960s America, racial segregation was still on going, black people were still being discriminated against and categorized into certain stereotypes. The movie Green Book (2018) depicts the experience of a black classical pianist’s experience at that time and the struggles he faced throughout his journey with his Italian-American chauffeur. The purpose of this study is to analyse the speech of the main character in the movie, Donald Shirley, using the Communication Accommodation Theory while fragmenting the identity of the same character throughout the movie to provide an understanding of the psychological journey Donald Shirley goes through. The approach used in this research is the historical approach as well as the cultural approach. The method used in this research was analytical, descriptive method; during the movie we observe that Donald Shirley used convergence in his speech to assert his eloquence while using divergence to assert his cultural background and individuality; he manages at the end to negotiate his identity and embrace his culture as a part of himself. The findings of the present study highlight the importance of sociolinguistic and social paradigms in providing insight into the understanding of the intricacies of this work